Pore-scale simulation of vortex characteristics in randomly packed beds using LES/RANS models. (23rd February 2018) - Linsong, Jiang; Hongsheng, Liu; Dan, Wu; Jiansheng, Wang; Maozhao, Xie
Highlights: A method is proposed to build real geometric structures of randomly packed beds. LES and RANS methods are employed to predict vortex shape and evolution features. Distribution characteristics of vorticity and velocity are analysed. The Q criterion is used to identify vortex structures and evolution of vortexes. The spatial scale of the maximum eddy and the time-scale of eddy merging are concluded. Abstract: Turbulent flow characteristics and vortex behaviors in the pore space of real packed beds under different flow conditions is numerically investigated. Real geometric structure of randomly packed beds is modeled using the discrete element software LIGGGHTS. Both LES and RANS methods are employed to predict vortex shape and evolution features at pore scale in actual packed beds. The numerical model is validated corresponding to experimental data, a good agreement is achieved between predicted results and measurements. Based on the computational results, the distribution characteristics of vorticity and velocity in multiple representative special structures are analysed, such as the channel formed by two pellets, similar triangle area formed by compact spherical walls and channel. Besides the effects of special structures on vortex shape and turbulence intensity is studied, such as the guiding and friction effect by the side spherical wall on gas motion, and strong shear force on both sides of the main channel. The Q criterion is used to identify vortex structures and capture distribution and evolution of vortexes in the computational domain. Moreover, the effect of inlet velocity on the position and shape of eddies is investigated, and eddy morphological changes under unsteady inlet conditions are also discussed., At last, a comparison between LES and RANS methods shows that the LES method can capture more details of the distribution and shape of the vortexes in the pore space, and therefore it is more suitable to the complicated flow field in porous media.